Comparison of Range of Motion (ROM) Limitations and Lymphedema in Breast Cancer Patients Following Axillary Lymph Node Dissection (ALND) and Sentinel Lymph Node Biopsy (SLNB): A Systematic Review - Rahmautami, I G A Gita Dewi; Wiraguna, I Gede Wikania; Irawan, Hendry; Tirtayasa, I Nyoman Wawan; Tulus Widiana, ⁠I Gede Tuban Eling (Syntax Corporation Indonesia, 2026)
Axillary lymph node dissection (ALND) and sentinel lymph node biopsy (SLNB) are widely used surgical procedures for breast cancer management. Previous studies have reported a lower incidence of range of motion (ROM) limitations and lymphedema following SLNB. However, no systematic review has been conducted to consolidate these findings. This research aims to systematically compare the incidence of ROM limitations and lymphedema in breast cancer patients undergoing ALND versus SLNB. The methods follow PRISMA 2020 guidelines, with a literature search conducted using PubMed, ScienceDirect, and Cochrane databases. The population included early-stage invasive breast cancer patients who underwent either SLNB or ALND. A qualitative analysis was performed to assess postoperative ROM limitations and lymphedema. Ten studies involving 8,523 patients were included. Both procedures were applied to patients with operable, early-stage invasive breast cancer. Qualitative analysis indicated that SLNB was generally associated with fewer postoperative complications, particularly in terms of ROM limitation and lymphedema. Some studies reported similar outcomes for both techniques regarding ROM limitation and lymphedema, but SLNB showed better outcomes in terms of postoperative complications such as lymphedema and ROM limitation. However, heterogeneity in definitions, assessment methods, lymph node involvement, and surgical techniques was noted across studies. This systematic review suggests that SLNB is associated with a lower incidence of ROM limitations and lymphedema compared to ALND, supporting its use as a less morbid surgical approach in early-stage breast cancer.